Evaluation of the Application Merdeka Curriculum in Economics Learning with Kirkpatrick Model at Sman 1 Grati Pasuruan and SMAN 1 Lawang Malang - Agustin, Linda; Mazidah, Nur; Rofiah, Siti Khusnul (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
This research is descriptive qualitative in nature which was prepared to provide an in-depth analysis regarding the implementation of the independent curriculum in economic learning in schools using the Kirkpatrick model with the research subjects being SMAN 1 Grati Pasuruan and SMAN 1 Lawang Malang. The results of the research show that the theoretical implication of the results of this research is that the Kirkpatrick model evaluation provides information about how to assess students' abilities as a whole. The practical implication is that the Kirkpatrick model evaluation is an alternative for teachers to get an idea of students' abilities in economics learning. Based on the evaluation results using the Kirkpatrick Model, both SMAN 1 Grati and SMAN 1 Lawang have been implemented well considering that both schools implemented the independent curriculum at different stages. These different stages make the objectives of implementing the independent curriculum that are applied also different, the higher the IKM stage that is implemented, the better the expectations and output achieved. This research has an impact on general learning evaluation for other subjects with the same characteristics. Assessment in each learning process is carried out in various ways to obtain an optimal picture of the student's inherent potential, especially those related to certain subjects. This is done to improve student learning outcomes.